Genetic analysis of pancreatic phospholipase A2 (PLA2G1B) in patients with chronic pancreatitis - Ewers, Maren; Epple, Denise; Bugert, Peter; Rosendahl, Jonas; Witt, Heiko (Pancreatology, 2022)
Background: Genetic mutations in various pancreatic enzymes or their counteracting proteins have been linked to chronic pancreatitis. In particular, variants in the genes encoding pancreatic lipase (PNLIP) and carboxyl ester lipase (CEL) have been associated with pancreatitis. Therefore, we investigated pancreatic phospholipase A2 (PLA2G1B) as a promising candidate gene in patients with chronic pancreatitis. Methods: We analyzed all coding exons and adjacent intronic regions of PLA2G1B in 416 German patients with non-alcoholic chronic pancreatitis (NACP) and 186 control subjects by direct DNA sequencing. Results: We detected 2 frequent synonymous variants in exon 3: c.222T>C (p.Y74 = ) and c.294G>A (p.S98 = ). The genotype and allele frequencies of these variants were similar between patients and controls (c.222 TC: 9.6% in NACP vs. 9.7% in controls; c.222CC: 0.2% in NACP vs. 0% in controls; c.294 GA: 31.3% in NACP vs. 28.0% in controls; c.294AA: 2.4% in NACP vs. 1.1% in controls). All p-values were non-significant. In addition, we found one synonymous variant, c.138C>T (p.N46 = ) and one non-synonymous variant, c.244A>G (p.S82G), in a single case each. Conclusions: Our results suggest that genetic alterations in PLA2G1B do not predispose to the development of non-alcoholic chronic pancreatitis.
Im Titel ist "(PLA2G1B)" in kursiver Schrift geschrieben
Online verfügbar: 7. Januar 2022, Artikelversion: 3. März 2022
Gesehen am 16.04.2024